Detection of EGFR Mutations From Plasma of NSCLC Patients Using an Automatic Cartridge-Based PCR System - Heeke, Simon; Hofman, Véronique; Benzaquen, Jonathan; Otto, Josiane; Tanga, Virginie; Zahaf, Katia; Allegra, Maryline; Long-Mira, Elodie; Lassalle, Sandra; Marquette, Charles-Hugo; Ilie, Marius; Hofman, Paul (Frontiers in Pharmacology, 2021)
The introduction of liquid biopsies for the detection of EGFR mutations in non-small cell lung cancer patients (NSCLC) has revolutionized the clinical care. However, liquid biopsies are technically challenging and require specifically trained personnel. To facilitate the implementation of liquid biopsies for the detection of EGFR mutations from plasma, we have assessed a fully automated cartridge-based qPCR test that allows the automatic detection of EGFR mutations directly from plasma. We have analyzed 54 NSCLC patients and compared the results of the cartridge-base device to an FDA-approved assay. Detection of EGFR mutations was comparable but slightly lower in the cartridge-based device for L858R mutations (14/15 detected, 93%) and exon 19 deletions (18/20 detected, 90%). Unfortunately, 8/54 (15%) tests failed but increasing the proteinase K volume helped to recover 3/4 (75%) unsuccessful samples. In summary, the fully automated cartridge-based device allowed the detection of EGFR mutations directly from plasma in NSCLC patients with promising accuracy. However, protocol adjustments are necessary to reduce a high test failure rate.